Speech Recognition as a Function of Age and Listening Experience in Adult Cochlear Implant Users. (27th May 2021) - Murr, Alexander T.; Canfarotta, Michael W.; O'Connell, Brendan P.; Buss, Emily; King, English R.; Bucker, Andrea L.; Dillon, Sarah A.; Rooth, Meredith A.; Dedmon, Matthew M.; Brown, Kevin D.; Dillon, Margaret T.
Abstract : Objectives/Hypothesis: Speech recognition with a cochlear implant (CI) tends to be better for younger adults than older adults. However, older adults may take longer to reach asymptotic performance than younger adults. The present study aimed to characterize speech recognition as a function of age at implantation and listening experience for adult CI users. Study Design: Retrospective review. Methods: A retrospective review identified 352 adult CI recipients (387 ears) with at least 5 years of device listening experience. Speech recognition, as measured with consonant‐nucleus‐consonant (CNC) words in quiet and AzBio sentences in a 10‐talker noise masker (10 dB signal‐to‐noise ratio), was reviewed at 1, 5, and 10 years postactivation. Results: Speech recognition was better in younger listeners, and performance was stable or continued to improve through 10 years of CI listening experience. There was no indication of differences in acclimatization as a function of age at implantation. For the better performing CI recipients, an effect of age at implantation was more apparent for sentence recognition in noise than for word recognition in quiet. Conclusions: Adult CI recipients across the age range examined here experience speech recognition benefit with a CI. However, older adults perform more poorly than young adults for speech recognition in quiet and noise, with similar age effects through 5 to 10 years of listening experience. Level of Evidence: 3 Laryngoscope, 131:2106–2111, 2021